Improved Min-Sum Algorithm for Raptor-Like LDPC codes in ATSC 3.0 - Ju, Hao; Xu, Yin; Zhang, Genning; He, Dazhi; Gao, Na; Zhang, Wenjun (IEEE International Symposium on Broadband Multimedia Systems and Broadcasting, 2019)
In order to improve the performance of low-rate LDPC codes, ATSC 3.0 adopted raptor-like structure. Min-sum (MS) algorithm and improved versions can be used directly, but their performance on raptor-like LDPC codes are disappointing. In this paper, we introduce an improved min-sum(IMS) algorithm for raptor-like LDPC codes in ATSC 3.0. Simulation results of frame error rate show that the IMS algorithm not only has a noticeable gain in waterfall region over normalized min-sum (NMS) algorithm and offset min-sun (OMS) algorithm, but also has almost the same time complexity. Different from OMS algorithm, the proposed algorithm is not sensitive to the imperfect channel estimation. Meanwhile, the IMS algorithm is easier to realize than those variable factors based algorithms.